Thoroughly Remold the Localization and Signaling Pathway of TLR22 - Ji, Jianfei; Liao, Zhiwei; Rao, Youliang; Li, Wenqian; Yang, Chunrong; Yuan, Gailing; Feng, Hao; Xu, Zhen; Shao, Jianzhong; Su, Jianguo (Frontiers in Immunology, 2020)
TLR22 exists in nearly all the poikilothermic vertebrates, playing a central role in the initiation of innate immunity and activation of adaptive immunity. TLR22 signaling pathway has been characterized in fugu (Takifugu rubripes) in detail. Here, we thoroughly remould the localization and signaling pathways of TLR22. We employed TLR22a and TLR22b in grass carp (Ctenopharyngodon idella), designated as CiTLR22a and CiTLR22b, explored the ligand(s), adaptor(s) and signaling pathway(s). Confocal fluorescence microscopy demonstrates that both CiTLR22a and CiTLR22b localize to lysosome. poly(I:C)-pull down and luciferase activity assays indicate that both CiTLR22a and CiTLR22b directly bind and respond to dsRNA analog poly(I:C). Fluorescence colocalization, CoIP experiments and bioinformatics analysis confirm that CiTLR22a and CiTLR22b interact with adaptor molecule MyD88, not TRIF or TIRAP. CiTLR22a facilitates protein and phosphorylation levels of IRF7 and enhances promoter activities of major IFNs and NF-κBs, in contrast, CiTLR22b inhibits IRF7 phosphorylation and IRF3 protein levels and suppresses IFNs and NF-κBs pathways. Further investigations reveal that CiTLR22a restrains grass carp reovirus (GCRV) replication and protects cells from GCRV infection, whereas CiTLR22b plays a negative role in response to GCRV infection. This is the first time to systematically clarify the signaling pathways of two isotype TLR22s, especially, subcellular localization and adaptor are different from previous TLR22 report, which results from technical progresses. The results will serve the antiviral immune mechanisms in poikilothermic vertebrates and evolutionary immunology.